Cell Receptors for Influenza a Viruses and the Innate Immune Response - Ramos, Irene; Fernandez-Sesma, Ana (Frontiers in Microbiology, 2012)
The interaction of the hemagglutinin (HA) of the influenza A viruses (IAV) with the cell surface is a key factor for entry of the virus and productive infection of the cell. This glycoprotein has affinity for sialic acids (SA), and different strains present specificity for SA bound through α2,3 or α2,6 linkages to the underlying sugar chain, which is usually related with host and cell tropism. Nucleic acid recognizing receptors (mainly RIG-I and Toll-like receptors) are the most extensively studied pattern recognition receptors for IAV. However, due to the ability of the HA of avian, swine or human influenza viruses to bind differently linked SA, and to the high levels and variability of glycosylations of their major virion glycoprotein components, the HA and NA, carbohydrate recognizing receptors in the cell membrane could also play an important role in initiating different signaling pathways to elicit the immune response in infected cells. But, at present, these interactions are not well understood. In this mini-review we discuss how the interactions of IAV with cell surface receptors on immune cells might be important for the induction of specific innate immune responses and as a result, for pathogenicity in humans.